2014
DOI: 10.1002/jaal.310
|View full text |Cite
|
Sign up to set email alerts
|

Kindle‐ing the Common Core

Abstract: This column features essays written by current middle school and high school teachers, media specialists, librarians, literacy coaches, curriculum specialists, administrators, preservice teachers, teacher educators, and adolescent and adult learners. They highlight diverse perspectives on teaching and/or learning with literacies to inspire reader reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The provisions of the bill also promoted the research of core literacy in this country [ 10 ]. Testa and Tonsing take cultivating students' core literacy of different ages as the educational goal, and draw up curriculum objectives and content through core literacy so as to lead the curriculum reform [ 11 ]. After research, Wurziger found that in some technology-oriented universities, there are many problems in the training methods of students' comprehensive ability, which leads some universities to attach importance to technology education but neglect the all-around development of students ability [ 12 ].…”
Section: Related Workmentioning
confidence: 99%
“…The provisions of the bill also promoted the research of core literacy in this country [ 10 ]. Testa and Tonsing take cultivating students' core literacy of different ages as the educational goal, and draw up curriculum objectives and content through core literacy so as to lead the curriculum reform [ 11 ]. After research, Wurziger found that in some technology-oriented universities, there are many problems in the training methods of students' comprehensive ability, which leads some universities to attach importance to technology education but neglect the all-around development of students ability [ 12 ].…”
Section: Related Workmentioning
confidence: 99%